Comparative Voices of Resistance: Gender and Power in Japanese and Balinese Novels (1989–2019) - I Gusti Ayu Andani Pertiwi; Ida Ayu Laksmita Sari; I Nyoman Suarka; Sachiko Takasaki (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The resistance to patriarchal domination in Japanese and Balinese societies between 1989 and 2019 is reflected in various literary works that portray women's struggles against restrictive social norms. In this vein, this study compares the forms and meanings of resistance depicted in the Japanese novels Out by Natsuo Kirino and Convenience Store Woman by Sayaka Murata with the Balinese novels Tempurung and Kenanga by Oka Rusmini. Using qualitative research with a cultural studies approach, it identifies two shared forms of resistance: rejection of traditional gender roles and struggle for bodily autonomy. Differences appear in the forms, with radical resistance in the Japanese novels and subversive resistance in the Balinese novels, and in the backgrounds, where structural oppression shapes the Japanese texts while traditional customs influence the Balinese texts. Ultimately, these narratives critique both Japanese patriarchy and Balinese customary traditions that constrain women’s identities and choices.